Phytochemical investigation of the leaves of tetracera scandens Linn and in vitro antidiabetic activity of hypoletin - Ahmed, Qamar Uddin; Umar, Abdulrashid; Bakhtiar, M. Taher; Darnis, Deny Susanti; Mohamed Amiroudine, Mohamed Zaffar Ali; Latip, Jalifah (Springer, 2014)
Tetracera scandens Linn. (Dilleniaceae), locally known as Mempelas Kasar, is traditionally used in folk remedies by various indigenous people in different countries including Malaysia for the treatment of rheumatism, inflammatory diseases, hepatitis, internal pains, urinary disorders, dysentery, sore throat, gout and diabetes infirmities; for lowering hypertension; and for child birth. In this study, phytochemical analysis of T. scandens leaf methanol (MeOH) extract was carried out for the first time and afforded three terpenoids (stigmasterol, betulinic acid and an isomeric mixture of sitosterol (∆5) glycoside and stigmasterol (∆5,22) glycoside) and six flavonoids (namely, kaempferol, quercetin, isoscutellarein, hypoletin, astragalin and kaempferol-3-O-(6″-O-p-trans-coumaroyl) glucoside, a rare compound which has been isolated for the first time from family Dilleniaceae). Structures of all compounds were elucidated through extensive UV–Vis, mass, IR and NMR spectral analysis. The occurrence of all these compounds is being reported for the first time from this plant. Due to the rare occurrence of hypoletin (3′,4′,5,7,8-pentahydroxyflavone) in plants, its in vitro antidiabetic effect was explored. Hence, the treatment of hypoletin in a dose-dependent manner was examined on the induction of lipid accumulation by using Oil Red O staining and glucose regulation in 3T3-L1 adipocytes in vitro with regard to its preventive role in the management of diabetes. After 8 days, morphological changes and high lipid accumulation activity were observed in cells treated with 10 μg/mL of hypoletin concentration (P < 0.01). In addition, the intracellular fat accumulation increased by up to 79.7 % relative to MDI-treated control cells at a dose of 10 μg/mL. Furthermore, insulin-induced 2-deoxy-d-[3H] glucose uptake was significantly increased (P < 0.001) in hypoletin-treated cells as compared to control (DMSO cells). Our results suggest that hypoletin could be useful for the management of type 2 diabetes due to its adipocyte stimulation and glucose uptake activity.